2021
DOI: 10.3389/fendo.2021.655982
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interactions Between the Immune System and the Neuroendocrine System in Health and Disease

Abstract: The immune system and the neuroendocrine system share many common features. Both consist of diverse components consisting of receptors and networks that are widely distributed throughout the body, and both sense and react to external stimuli which, on the one hand control mechanisms of immunity, and on the other hand control and regulate growth, development, and metabolism. It is thus not surprising, therefore, that the immune system and the neuroendocrine system communicate extensively. This article will focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Recently, an increasing number of studies in mammals have revealed that excitatory and inhibitory neuroendocrine factors can antagonistically regulate the activity of cell movement in addition to together supporting the behavior of animal movement ( 59 , 77 ). Excitatory neuroendocrine factors such as L-adrenaline and L-dopamine induce the cell migration of embryonic neural progenitor cells through the activation of α1 adrenergic receptors and the dopamine D1 receptor, respectively ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of studies in mammals have revealed that excitatory and inhibitory neuroendocrine factors can antagonistically regulate the activity of cell movement in addition to together supporting the behavior of animal movement ( 59 , 77 ). Excitatory neuroendocrine factors such as L-adrenaline and L-dopamine induce the cell migration of embryonic neural progenitor cells through the activation of α1 adrenergic receptors and the dopamine D1 receptor, respectively ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones exert pleiotropic effects on immune response. Previous studies have identified thyroid hormone effects on the functions of both innate immune cells (e.g., granulocytes, natural killer cells, macrophages, and dendritic cells) and adaptive immune cells (e.g., T-and B-lymphocytes) [23]. Here, we focus on macrophages and T-lymphocytes, which have been recognized as important determinants in the pathogenesis of atherosclerosis [24,25].…”
Section: Thyroid Hormone Status and Immune Response In Atherosclerosismentioning
confidence: 98%
“…The concept of general health can thus be easily explained by detailing the basic concepts of these components which stabilize the wellbeing. Tridosha [6] The concept of Tridosha is related to physiological regulation through the unified functioning of the Doshas namely Vata, Pita and Kapha. Essentially Dosha plays a vital role in maintaining health and manifestation of diseases.…”
Section: General Health-basic Concepts In Ayurvedamentioning
confidence: 99%